Measurements of formant bandwidths in the time domain - Nord, Lennart (Annual Report of the Institute of Phonetics University of Copenhagen, 1978)
Two methods of estimating formant bandwidth in the time domain were tried. The vocal tract with the glottis closed was excited, either by pulses or by a gated sine wave signal, with its frequency adjusted to one of the resonances of the vocal tract. Bandwidth values were obtained from the decay curves. Measurements on Swedish vowels, articulated by two male and two female speakers were performed and the results compared to sweep-tone measurement data.